Very low high-density lipoprotein-cholesterol and long-term mortality. (14th October 2021) - Dykun, I; Hendricks, S; Babinets, O; Al-Rashid, F; Totzeck, M; Rassaf, T; Mahabadi, A A
Abstract: Background: High-density lipoprotein-cholesterol (HDL-C) has anti-atherogenic, anti-inflammatory, anti-oxidative, anti-apoptotic, and vasodilatory properties. While a linear inverse relationship between HDL-C levels and all-cause mortality is established, recent observational studies suggest a U-shaped association between HDL-C and outcome. Purpose: We tested the hypothesis that both low and high HDL-C levels associate with long-term mortality. Methods: The present analysis is based on the longitudinal ECAD registry of consecutive patients undergoing coronary angiography at the West German Heart and Vascular Center between 2004 and 2019. HDL-C was quantified at hospital admission using standardized enzymatic methods. The incidence of death due to any cause was evaluated during follow-up. Cox regression analysis was used to determine the association of HDL-C with incident mortality, adjusting for age, sex, systolic blood pressure, low-density lipoprotein cholesterol, smoking status, and family history of premature cardiovascular disease. In addition to the analysis on HDL-C as continuous variable, the association of HDL-groups (<10th percentile, 10th-<25th percentile, 25th-<50th percentile, 50th-<75th percentile, 75th-90th percentile, and ≥90thpercentile) with incident mortality was determined using HDL-C <10th percentile as reference. Results: Among 17, 433 patients, mean age was 65.9±12.6 years and 70.1% were men. Mean HDL-C was 48.7±16.2 mg/dL. During a mean follow-up 3.38±2.10 years, 2, 401 patients (13.8%) died. In multivariable analysis, higher HDL-C levels were independently associated with lower all-cause mortality [hazard ratio (95% confidence interval): 0.83 (0.76, 0.91) per 1 standard deviation change in HDL-C, p<0.001]. Associations between HDL-C and mortality were equally present in male [0.83 (0, 74, 0.93), p=0.001] and female patients [0.85 (0.73, 1.00), p=0.0496]. Using HDL-C <10thpercentile as reference (<31mg/dl), all other HDL-C groups showed stable effect sizes below 1.0 without signs of increasing morality probability in high HDL-C groups [0.50 (0.44, 0.58), p<0.001; 0.41 (0.36, 0.46), p<0.001; 0.37 (0.32, 0.42), p<0.001; 0.36 (0.36, 0.31), p<0.001; and 0.40 (0.34, 0.47), p<0.001 for HDL-C 31–37 mg/dL, 38–45 mg/dL, 46–56 mg/dL, 57–69 mg/dL, and ≥70mg/dl, respectively]. Conclusions: In a large longitudinal registry cohort of patients undergoing invasive coronary angiography, only very low HDL-C levels were associated with increased long-term mortality. We found no signs of a U-shaped association between HDL-C and prognosis. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Iryna Dykun was supported by the German Research Foundation (DY 149/2-1)Stefanie Hendricks was supported by the Universitätsmedizin Essen Clinician Scientist Academy (UMEA)